Fieldwork on the Mlabri language: A preliminary sketch of its phonetics - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
The present report deals with the phonetics of the Mlabri ("Mrabri") language spoken by a small hill tribe in Northern Thailand. This informal sketch gives an impressionistic phonetic survey of the vowel and consonant systems; more definitive analyses of this and other aspects of the language will be worked out later by the research group, viz. Professor Søren Egerod, Professor Therapan L. Thongkum, and the present author.